Quality of life in patients with neurofibromatosis type 1: a nationwide database study in Japan from 2015 to 2019 - Takashi Yamauchi; Machi Suka (Komiyama Printing Co. Ltd, 2023)
Background: This study examined the association between dermatological, neurological, and bone manifestations of neurofibromatosis type 1 (NF1) and quality of life (QoL) in patients with NF1 using a nationwide database of all patients who newly claimed for medical expense subsidies in Japan from 2015 to 2019. Methods: The Japanese Ministry of Health, Labour and Welfare provided the "National Database of Designated Intractable Diseases of Japan" containing clinical and personal records ("Medical Certificates of Designated Intractable Diseases") of all patients with NF1 following approval of the study protocol. To examine the association between the severity of symptoms and QoL, multinominal logistic regression analyses were performed, adjusted for potential confounders. Results: The final study population consisted of 1,487 patients (775 females and 712 males; mean (standard deviation) age, 45.4 (17.9) years). More than 50% and nearly 45% of participants were recorded as having moderate or severe "pain/discomfort" and "anxiety/depression," respectively. The severity of neurological symptoms was significantly associated with all components of QoL, whereas the severity of dermatological symptoms was significantly associated with only moderate or severe subjective and mental health-related components of QoL, and the severity of bone lesions was associated with only moderate or severe physical health-related components of QoL. Subjective and mental health-related components of QoL tended to be deteriorated more than physical health-related components of QoL in younger and female patients. Conclusions: Severities of neurological and dermatological symptoms were significantly associated with subjective and mental health-related components of QoL, while the severity of bone symptoms was associated with only moderate and severe deterioration of physical health-related components of QoL.